2022
DOI: 10.1590/0034-7167-2021-0418
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about flushing for intravenous catheter maintenance in hospitalized adults?

Abstract: Objective: to evidence the use of flushing to prevent complications from intravenous therapy. Methods: an integrative review in databases, using descriptors and selection criteria. Data were collected in 12 articles using an instrument and later classified, summarized and aggregated for knowledge synthesis. Results: it was evident that: the pre-filled syringe resulted in a lower occurrence of catheter obstruction; irregular flushing frequency caused advanced phlebitis; the use of Venous Arterial Blood Manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) tool was used to present the data of this stage. The second stage consisted of analyzing this practice for the existence of errors, using the following references: for the identification of potential errors, the Infusion Nurses Society (INS) 1,6 international guidelines and Brazilian National Health Regulatory Agency (ANVISA -Agência Nacional de Vigilância Sanitária) 5 national guidelines on good practices related to flushing as well as an integrative literature review by the authors; 10 and, for the analysis of these errors, James Reason's safety incident analysis model 11 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) tool was used to present the data of this stage. The second stage consisted of analyzing this practice for the existence of errors, using the following references: for the identification of potential errors, the Infusion Nurses Society (INS) 1,6 international guidelines and Brazilian National Health Regulatory Agency (ANVISA -Agência Nacional de Vigilância Sanitária) 5 national guidelines on good practices related to flushing as well as an integrative literature review by the authors; 10 and, for the analysis of these errors, James Reason's safety incident analysis model 11 .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, an integrative review of publications carried out between 2016 and 2020 found that there are still disagreements about the volume, frequency, preparation solution, technique and devices for performing flushing. In particular, in the Brazilian scenario, no research developed on the subject in this period was identified 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In addition, an integrative literature review of publications on flushing between 2016 and 2020 did not identify research carried out in the Brazilian context on flushing in this period. 18 This shows that, in Brazil, there is a lack of research on the topic. Therefore, there is a need for more evidence on implementing flushing at the national level, with a view to adopting strategies that strengthen its practice among professionals and increase patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, existing research has generically evaluated the practice of flushing, that is, only verifying whether it is performed as one of the stages of administration of intravenous therapy without a more profound examination of the characteristics of this practice and the factors associated with its application 16,17. In addition, an integrative literature review of publications on flushing between 2016 and 2020 did not identify research carried out in the Brazilian context on flushing in this period 18…”
Section: Introductionmentioning
confidence: 99%